Outside your window : a first book of nature - Davies, Nicola, 1958-; Hearld, Mark (Somerville, Mass. : Candlewick Press, 2012)
An illustrated treasury of poems reflects the experiences of children as they encounter nature for the first time.
Kirkus Review
Pub Weekly
Kirkus Review, January 2012
Pub Weekly, January 2012
2.3
K-3
Keywords: Nature -- Juvenile poetry; Nature -- Poetry; Nature poetry; Picture books for children